STUDY OF AUXILIARY GAS PRESSURE ON LASER CUTTING TECHNOLOGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Two types of electrical sheet steel M250-35A and M530-50A were used to cut by melting with a TruLaser 1030 technological system. It was observed that pressure of auxiliary gas had a major effect on kerf width b and cut angle deviation α. Nitrogen as an assisted gas has been taken. The basic parameters as laser power, cutting speed, focus position were constantly supported and the pressure was changed from 4 bar to 20 bar by step 2 bar. As well as the experimental results of gas pressure on entrance and exit kerf widths, have been analyzed and discussed in this study.